The Influence of Accounting Conservatism, Fixed Asset Density, and Firm Size onTax Aggressiveness - Syahputera, Kelvin Adi; Halim, Sofyan (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This study aims to analyze the influence of accounting conservatism, fixed asset intensity, and company size on tax aggressiveness in non-cyclical companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2022 period. This study is based on the importance of understanding the factors that influence a company's tax planning strategy, especially in the context of tax aggressiveness. This study uses a quantitative approach with a descriptive method. The research sample was selected using purposive sampling, with a total of 102 non-cyclical companies meeting the criteria. The data used is in the form of secondary data from financial statements published in www.idx.com. Independent variables include accounting conservatism, fixed asset intensity, and company size, while the dependent variable is tax aggressiveness. Data analysis was carried out by descriptive statistics, classical assumption tests, multiple regression analysis, correlation and determination coefficient analysis, and hypothesis tests (t-test and F-test). The results of the study show that accounting conservatism, fixed asset intensity, and company size have no effect on tax aggressiveness. These findings indicate that these factors are not the main determinants in aggressive tax planning strategies for non-cyclical companies in Indonesia.